THE CATALOGUES ANALYSIS OF STARS EQUATORIAL COOR-DINATES AND B-MAGNITUDE OF THE FON PROJECT - Akhmetov, V. S.; Khlamov, S. V.; Andruk, V. M.; Protsyuk, Yu. I. (Одеські астрономічні публікації, 2018)
The comparison results of three catalogues (FON-KIEV, FON-KITAB and FON-DUSHANBE) were received as result of work of the FON project and presented in the paper. The data of zero zone (from -2 to 2 degrees of declination) from the mentioned catalogues was used during the research. The number of common objects after cross-match of catalogues with a circular search window equals to 1.5 arc seconds was more than 500 thousands. The estimation of random accuracy of stars positions from the mentioned catalogues was performed by the Wielen method. Final dispersions were calculated for every sub-range of magnitudes. The stars with individual differences of position and magnitude that exceed three standard deviations were rejected. The data from catalogues РМА was used for estimation of the systematic errors. It is obvious that the internal estimates of position accuracy of stars in the compared catalogues are low in one or all catalogues, and additional research is required. Analysis of the behavior of the systematic differences and standard deviations of the stellar positions of these catalogues have shown that there are a big values reaching 1 arcsec only in small sky regions. However, the internal accuracy that presented in catalogues is well matched with the systematic differences and standard deviations in the other sky regions. Astrometry, astrometry-catalogue, data analysis.